Disponibilidade hídrica e a dinâmica urbano-regional do Semiárido brasileiro - Sérgio Domiciano Gomes de Souza; Anny Catarina Nobre de Souza; Maria Losângela Martins de Sousa (Confins)
The paper analyzes the water availability of the Brazilian Semiarid region in the face of its water infrastructure and the challenges of the new urban-regional dynamics, through a bibliographic, documentary and cartographic production research, together with the data collection from the main surface reservoirs, wells and social technologies in the area. It was found that the Semiarid region has historically been the target of water infrastructure policies for different uses, which in turn are concentrated in some states, although they contemplate all of them. Recently, this territory has undergone transformations, aggregating population flows and productive arrangements, which demand increasing needs in the urban-regional context. Thus, the water issue in the Semi-arid region remains a challenge for management, capable of making the existing water infrastructure compatible with the growing demands of the new urban-regional dynamics, in the context of the vulnerability of climate droughts.